Educating agricultural researchers: a review of the role of African universities - Beintema, Nienke M.; Pardey, Philip G.; Roseboom, Johannes (International Food Policy Research Institute, 1998)
The number of higher-education institutions and the students enrolled in them has grown rapidly throughout Africa since the early 1960s. The number of universities increased from less than 20 in 1960 to nearly 160 by 1996; student numbers grew from 119,000 to almost two million over the same period, yet enrollment ratios in Africa continue to lag well behind developed and other-developing country norms. Funding for higher-education in Africa kept pace with the expanding institutional base during the 1960s and 1970s, but has fallen well behind the growth in student numbers since 1980. The pattern of the development of the agricultural sciences has matched the general pattern of development of the higher-education sector. Three quarters of the countries in Africa currently offer some tertiary training in the agricultural sciences. Only one half of the African faculties of agricultural sciences offer postgraduate degrees, and most of these programs were established in the past decade. Nonetheless, much of the rapid growth in the number of national scientists working in national agricultural research institutes continues to rely on scientists trained to the postgraduate (and also BSc) level outside the region.